Religious Pluralism in Ghana: Using the Accommodative Nature of African Indigenous Religion (AIR) as a Source for Religious Tolerance and Peaceful Coexistence - Samuel Kofi Boateng Nkrumah-Pobi; Sandra Owusu-Afriyie (International Journal of Interreligious and Intercultural Studies, 2020)
This article deploys the accommodative nature of African Indigenous Religion (AIR) as a reflective tool in Ghana’s religious pluralistic context. This paper argues that the accommodative nature of AIR which has made scholars argue for its singularity can serve as a tool which would promote religious tolerance and peaceful coexistence in Ghana. The findings of the research demonstrated that though there is a level of religious tolerance and peaceful coexistence among various religious groups in Ghana, there is still more room for improvement, thus the proposal of this model as a response.